PERKEMBANGAN MASYARAKAT TRANSMIGRASI DI DUSUN SIDOMULYO DESA LIMBUNG KECAMATAN SUNGAI RAYA KABUPATEN KUBU RAYA (1955-2019) - Fitriani, Fitriani; Firmansyah, Andang; Putri, Astrini Eka (Universitas Tanjungpura, 2022)
AbstractThe research method used in this research is thehistorical research method (historical methodology). Thesteps used in the historical method consist of topicselection, heuristics, verification, interpretation, andhistoriography. From this research, it is concluded thatthe transmigration settlement was formed as a result ofthe transmigration program in 1955-1957. The aim of thetransmigration program is to change the standard ofliving for the welfare of the transmigrants for the better.Each head of a transmigrant family gets 50 square metersof land for the yard, and one hectare for agricultural landas well as a 10-year living allowance. The hard work oftransmigrants in adapting to the new environment is noteasy. Developments in terms of social and economicdevelopment are quite developed, with the existence ofcommunity social activities that continue to run tomaintain friendship between fellow people, although nowmany first generation transmigrants are no longer there,but most of the objects of transmigration are inhabited bydescendants of transmigrants and live side by side witheach other. with descendants of the original inhabitantsas well as immigrants. In the economic field, the peoplewho initially only made a living as farmers are nowworking as private employees, civil servants, TNI/POLRI.Although most of them still make a living as vegetablefarmers or gardening, but now they are classified assuccessful farmers with a promising income every timethey harvest.Keywords: Social Development, Economic Development,Transmigration.